Amelioration of olfactory dysfunction in a mouse model of Parkinson’s disease via enhancing GABAergic signaling - Xing-Yang Liu; Ke Wang; Xian-Hua Deng; Yi-Hua Wei; Rui Guo; Sui-Feng Liu; Yi-Fan Zhu; Jia-Jun Zhong; Jing-Yuan Zheng; Meng-Dan Wang; Qiu-Hong Ye; Jian-Quan He; et al. (Cell & Bioscience, 2023)
Abstract Background Olfactory dysfunction is among the earliest non-motor symptoms of Parkinson’s disease (PD). As the foremost pathological hallmark, α-synuclein initiates the pathology in the olfactory pathway at the early stage of PD, particularly in the olfactory epithelium (OE) and olfactory bulb (OB). However, the local neural microcircuit mechanisms underlying olfactory dysfunction between OE and OB in early PD remain unknown. Results We observed that odor detection and discrimination were impaired in 6-month-old SNCA-A53T mice, while their motor ability remained unaffected. It was confirmed that α-synuclein increased and accumulated in OB but not in OE. Notably, the hyperactivity of mitral/tufted cells and the excitation/inhibition imbalance in OB were found in 6-month-old SNCA-A53T mice, which was attributed to the impaired GABAergic transmission and aberrant expression of GABA transporter 1 and vesicular GABA transporter in OB. We further showed that tiagabine, a potent and selective GABA reuptake inhibitor, could reverse the impaired olfactory function and GABAergic signaling in OB of SNCA-A53T mice. Conclusions Taken together, our findings demonstrate potential synaptic mechanisms of local neural microcircuit underlying olfactory dysfunction at the early stage of PD. These results highlight the critical role of aberrant GABAergic signaling of OB in early diagnosis and provide a potential therapeutic strategy for early-stage PD.